Il Settecento portoghese e lusofono - Graziani, Michela (Studi e saggi, 2023)
The volume aims to fit into the existing studies in Italy and Portugal on the Portuguese 18th century, however describing the 18th century from a new, inclusive (and no more separatist), point of view between Portugal, Macao (in the south of China) and Brazil. The related insight does not have the claim to completeness, but offers an overview, allowing the lector to range over three Lusitanian territories. According to this principle of completeness, the volume is divided in three chapters within which historical, iconographical and literary themes of the 18th century are illustrated. The volume higlights historical facts, literary works, also through an European view of the same period, that have marked the Portuguese, Asian and Brazilian 18th century.